2016
DOI: 10.1182/blood-2016-05-717355
|View full text |Cite
|
Sign up to set email alerts
|

Clinicogenetic risk models predict early progression of follicular lymphoma after first-line immunochemotherapy

Abstract: • The posttreatment end point progression of FL within 24 months (POD24) is strongly associated with OS.• A pretreatment clinicogenetic risk model (m7-FLIPI) predicts POD24 and OS and identifies the smallest subgroup with highest unmet need.Follicular lymphoma (FL) is a clinically and molecularly heterogeneous disease. Posttreatment surrogate end points, such as progression of disease within 24 months (POD24) are promising predictors for overall survival (OS) but are of limited clinical value, primarily becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
2
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 191 publications
(167 citation statements)
references
References 26 publications
8
152
2
5
Order By: Relevance
“…Of all previously published numerical alterations in FL, only gain of chromosome 18 stood out as an independent prognostic marker. Our results confirm EZH2 as a strong prognostic marker in FL, with wild-type gene status associated with poor disease outcome (EF), 31,32 but other markers, such as EP300 and TNFRSF14, which have been implicated to have a significant, though minor, impact on prognosis, were not substantiated in our study. 31,54 This is likely due to selection bias and relative underrepresentation of poor prognosis patients in previous series for which our study design was specifically optimized.…”
Section: P-value and Fdrcontrasting
confidence: 45%
See 2 more Smart Citations
“…Of all previously published numerical alterations in FL, only gain of chromosome 18 stood out as an independent prognostic marker. Our results confirm EZH2 as a strong prognostic marker in FL, with wild-type gene status associated with poor disease outcome (EF), 31,32 but other markers, such as EP300 and TNFRSF14, which have been implicated to have a significant, though minor, impact on prognosis, were not substantiated in our study. 31,54 This is likely due to selection bias and relative underrepresentation of poor prognosis patients in previous series for which our study design was specifically optimized.…”
Section: P-value and Fdrcontrasting
confidence: 45%
“…Statistically significant differences after multiple testing correction were only found for gain of chromosomal region 18p11. 32 …”
Section: Impact Of Chromosomal Copy Numbers and Gene Mutations By Promentioning
confidence: 99%
See 1 more Smart Citation
“…1 Several studies identified a high-risk population of patients, comprising ;20% of all patients with NHL, who had FL that progressed within 24 months from initiation of the first-line chemoimmunotherapy and were at increased risk of death. [2][3][4] Idelalisib, a highly selective, orally bioavailable inhibitor of the d isoform of phosphoinositide 3-kinase d, is indicated in the United States and Europe as monotherapy for relapsed FL. 5,6 A phase 2, multicenter, open-label, single-arm study evaluated the efficacy and safety of idelalisib in 125 patients previously treated with first-line chemoimmunotherapy who had relapsed indolent NHL that was refractory to both alkylators and rituximab (NCT01282424).…”
mentioning
confidence: 99%
“…Early progression, most commonly defined as progression within 2 years after starting rituximabchemotherapy, occurs in ;20% of patients and has recently been associated with poor outcome. [6][7][8][9] Similarly, transformation to aggressive lymphoma, occurring in 2% to 3% of patients per year, has repeatedly been linked to adverse prognosis when compared with patients not experiencing transformation. [10][11][12][13][14][15] There is an association between early progression and transformation.…”
Section: Medscape Continuing Medical Education Onlinementioning
confidence: 99%